The Relationship Between Executive Functions and Academic Performance in Primary Education: Review and Meta-Analysis - Cortés Pascual, Alejandra; Moyano Muñoz, Nieves; Quílez Robres, Alberto (Frontiers in Psychology, 2019)
The purpose of this study was to research the relationship between executive functions and academic performance in primary education (6-12 years). Based on 21 samples (n = 7,947), a meta-analysis of random effects demonstrated a moderately significant weighted effect size (r = .365) and was found to be a good predictor of academic performance. For the subjects of language and mathematics, the results of the random effects model were similar and slightly higher for mathematics (r = .350; r = .365). Thus, the theory that executive functions have greater influence on mathematical performance is supported, especially in aspects such as coding, organization and the immediate retrieval of information. Regarding the different executive function components (working memory, inhibition, cognitive flexibility, and planning), working memory had the highest presence (k = 14, n = 3,740) and predictive weight for performance, with an effect size of r = .370 for random effects, with a moderate level of significance. The moderating effect of variables such as gender and age were also analyzed. After performing a meta-regression, gender resulted in a value of R² = .49; the age variable was not significant. This result is especially important since age has traditionally been considered to be the moderating variable of executive functions. The review reveals a good predictive power of executive functions in the primary education stage, and it is even higher at the early ages, indicating its great significance in describing future performance. The study also revealed the competencies and specific aspects of the executive functions that affect the way in which its components intervene in the academic area, demonstrating the mediating effect of variables such as physical fitness, motor skills and memory processes.